2006
DOI: 10.1371/journal.pmed.0030144
|View full text |Cite
|
Sign up to set email alerts
|

Getting It Right: Being Smarter about Clinical Trials

Abstract: A major NIH meeting led to recommendations for conducting better clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Since there is some indication that the way evidence is presented affects the likelihood of physicians changing their prescribing, 1−5 it is important that CME programs present evidence completely as recommended by the National Institutes of Health. 6 Such a change will require addressing the needs of learners and faculty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is some indication that the way evidence is presented affects the likelihood of physicians changing their prescribing, 1−5 it is important that CME programs present evidence completely as recommended by the National Institutes of Health. 6 Such a change will require addressing the needs of learners and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have found that family physicians and specialists consider therapy more effective, and may be more likely to make inappropriate practice changes, when data are presented in relative terms such as relative risk reduction rather than in absolute terms such as absolute risk reduction and number needed to treat (NNT). 1−5 The authors of these papers and the National Institutes of Health 6 suggest that no one measure provides the information necessary for physicians to make an informed decision about results of clinical trials. They suggest that data be presented in absolute and relative terms.…”
mentioning
confidence: 99%
“…Such a threshold could be met by requiring fundamental validity trials. 53 This would strengthen the link between surrogate and true clinical endpoints for commonly employed surrogates such as LDL and hemoglobin A1c levels. Even when established for one drug class (for example, LDL cholesterol and statins), the same surrogate may be a poor choice for a drug class that works through a different mechanism of action (for example, LDL cholesterol and ezetimibe).…”
Section: Policy Recommendationsmentioning
confidence: 86%
“…Statisticians’ roles in the design, analysis and reporting of pharmaceutical research spans the whole range of clinical studies from phase 1, including first‐in‐man studies, to major prelicensing phase 3 trials for regulatory approval, as well as preclinical animal studies and post‐licensing pharmacoepidemiology and pharmacovigilance. Drug safety issues can emerge preclinically, or only post licensing (Kramer et al. , 2006) when their emergence may call into question past regulatory decisions (Dhaun et al.…”
Section: Introduction: History and Remitmentioning
confidence: 99%
“…Statisticians in the pharmaceutical industry, and in regulatory authorities (Cochrane Collaboration, 2006; Food and Drug Administration, 2006; Ioannidis et al. , 2004; Kramer et al. , 2006; O'Neill, 2002), thus have a key role in enhancing the scientific and ethical quality of all these phases of pharmaceutical research.…”
Section: Introduction: History and Remitmentioning
confidence: 99%